2018
DOI: 10.1007/s11596-018-1900-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Transforming Growth Factor-βl and Arginase-1 Levels with Long-term Survival after Kidney Transplantation

Abstract: In this study, we compared the serum levels of transforming growth factor-pi (TGF-β1), interleukin-10 (IL-10), and arginase-1 in long-term survival kidney transplant recipients (LTSKTRs) with those in short-term survival kidney transplant recipients (STSKTRs). We then evaluated the relationship between these levels and graft function. Blood samples were collected from 50 adult LTSKTRs and 20 STSKTRs (graft survival approximately 1-3 years post-transplantation). All patients had stable kidney function. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…In line with our results, the minor alleles of these TGFB1 polymorphisms have also been suggested to lead to lower levels of TGF-β1 [ 30–32 ]. Furthermore, Du et al reported that long-term survival kidney transplant recipients had higher TGF-β1 levels than short-term survival kidney transplant recipients [ 18 ]. Serum TGF-β1 levels positively correlated with long-term graft survival and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our results, the minor alleles of these TGFB1 polymorphisms have also been suggested to lead to lower levels of TGF-β1 [ 30–32 ]. Furthermore, Du et al reported that long-term survival kidney transplant recipients had higher TGF-β1 levels than short-term survival kidney transplant recipients [ 18 ]. Serum TGF-β1 levels positively correlated with long-term graft survival and function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genetic deficiency of TGF-β1 in mice leads to multiorgan inflammation (including that of the kidney) [ 17 ]. In the context of these findings, Du et al found that TGF-β1 plasma levels were positively associated with long-term graft survival in kidney transplant recipients [ 18 ]. Finally, local TGF-β1 expression in the kidney allograft during rejection has been associated with a favourable outcome [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In kidney transplantation, TGF-β1 has been a topic of interest and most investigators believe that TGF-β1 affects allograft survival in different ways ( 37 ). It has been shown that TGF-β1 cells are closely associated with the short-term prognosis of clinical kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mice engineered to express epithelial-targeted, inducible, constitutively active TGF-b receptor I exhibit acute tubular injury and apoptosis, phenotypic dedifferentiation, synthesis of profibrotic factors, and interstitial inflammatory cell recruitment (45). In transplant-associated renal ischemia/ reperfusion injury, TGF-b1 initiates early repair and regeneration but in the setting of chronic inflammation drives continual matrix deposition and remodeling, leading to fibrotic disease, compromised renal function, and eventual organ rejection (46). Excessive ECM accumulation also provides a source of damage-associated molecular pattern ligands for the inflammatory response TLR (47)(48)(49)(50).…”
Section: The Renal Fibrotic Microenvironmentmentioning
confidence: 99%